University of the Philippines Elementary School grade six pupils a descriptive profile - Phumisuwan, Wongjuntara 1941-
Profile of the Grade Six pupils of the University of the Philippines Elementary School, located in Diliman, Quezon City was presented in this study. It is categorized into three major parts, namely, a) the pupils' physical characteristics as to age,sex, height, weight, ordinal position among the siblings in the family and social relationships; b) the educational, social, economic, and environmental background of their families, and, c) the pupils scholastic performance from the first to the fifth grade. The last part included the scholastic ratings of same group of pupils during the first and second grading periods while already in the sixth grade.